Crocodile tears eaudiobook - Horowitz, Anthony (Alex Rider, 2010)
Alex Rider thinks he has completed his final mission for MI6. But when a journalist threatens to expose his past, he is forced to return to his life as a teenaged spy. MI6 agrees to protect Alex in return for his help investigating a high-profile laboratory specializing in modified plant genes. Now Alex is up against a con man who plans to create a catastrophe with a genetically engineered virus to profit through a disaster-relief charity. In order for Alex to stop the virus from sweeping across the country, he'll have to brave gunfire, explosions, car crashes, and dangerous mercenaries—then come face to face with the deadly mastermind behind it all.